2019
DOI: 10.1186/s13690-019-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Low consumption of fruits and vegetables among adults in Uganda: findings from a countrywide cross-sectional survey

Abstract: IntroductionAdequate consumption of fruits and vegetables has protective benefits against development of coronary heart disease, hypertension and chronic obstructive pulmonary disease. However, approximately 2.7 million deaths annually can be attributed to inadequate fruit and vegetable consumption. We analyzed data from a countrywide survey in Uganda, to estimate the prevalence of adequate fruit and/ or vegetable consumption, and identify associated factors.MethodsData were collected using the World Health Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 27 publications
4
44
0
2
Order By: Relevance
“…28 The mean consumption of fruits and vegetables in our study are in line with a previous study in Uganda, which showed that only 12.2% of subjects consumed five or more servings of fruit and vegetables per day in a 'typical' week. 29 Demographic variables were similar between individuals with low and high AChE/Hb, making it less plausible that other variables co-vary enough with AChE/Hb to be responsible for the demonstrated associations. Theoretically, the relationship between AChE/Hb and HbA 1c could be biassed if both HbA 1c and AChE/Hb were affected by Hb levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28 The mean consumption of fruits and vegetables in our study are in line with a previous study in Uganda, which showed that only 12.2% of subjects consumed five or more servings of fruit and vegetables per day in a 'typical' week. 29 Demographic variables were similar between individuals with low and high AChE/Hb, making it less plausible that other variables co-vary enough with AChE/Hb to be responsible for the demonstrated associations. Theoretically, the relationship between AChE/Hb and HbA 1c could be biassed if both HbA 1c and AChE/Hb were affected by Hb levels.…”
Section: Discussionmentioning
confidence: 97%
“… 28 The mean consumption of fruits and vegetables in our study are in line with a previous study in Uganda, which showed that only 12.2% of subjects consumed five or more servings of fruit and vegetables per day in a ‘typical’ week. 29 …”
Section: Discussionmentioning
confidence: 99%
“…EFA deficiency is determined by the triene-to-tetraene ratio, or mead acid/AA, and a ratio of 0.02 is a clinical marker of EFA deficiency [35]. The lack of EFA deficiency in this population indicates that these children are receiving adequate amounts of EFAs through their diet [13]. This may be a result of Kampala being an urban area and therefore a larger variety of foods are available for consumption.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization (FAO), 89% of households in Uganda are food secure, however, nutritional awareness remains low [12]. For example, fruit and vegetable consumption by adults is low throughout Uganda, and approximately 90% of adults consume less than the recommended 5 servings of fruits and vegetables per day [13]. This may extend to children as well, negatively impacting growth.…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a los indicadores del riesgo de diabetes, los que presentaron mayor vulnerabilidad fue el bajo consumo de frutas y la falta de actividad física. Nuestros resultados coinciden con el estudio de Kabwama y colaboradores (27) , quienes evidencian un bajo consumo de frutas y verduras en Uganda -África, el cual puede ocasionar riesgos en la salud de su población. Según la Organización Mundial de la Salud (28) , aproximadamente 2,7 millones de muertes anuales pueden atribuirse al consumo inadecuado de frutas y verduras, esta cifra incluye el 11% de los accidentes cerebrovasculares y el…”
Section: Discussionunclassified